2019
DOI: 10.3390/jcm8040438
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors and Oncologic Outcome of Downgrade to Pathologic Gleason Score 6–7 after Radical Prostatectomy in Patients with Biopsy Gleason Score 8–10

Abstract: Gleason score (GS) 8–10 is associated with adverse outcomes in prostate cancer (PCa). However, biopsy GS (bGS) may be upgraded or downgraded post-radical prostatectomy (RP). We aimed to investigate predictive factors and oncologic outcomes of downgrade to pathologic GS (pGS) 6–7 after RP in PCa patients with bGSs 8–10. We retrospectively reviewed clinical data of patients with bGS ≥ 8 undergoing RP. pGS downgrade was defined as a pGS ≤ 7 from bGS ≥ 8 post-RP. Univariate and multivariate cox regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Based on that, the authors suggested that Bx grade could add additional prognostic value and may be used for risk stratification. Chung et al 13 in another study also reported an adverse impact of downgrading on biochemical recurrence, with 38% (332/860) of PCa patients downgraded to GS ≤ 7 at time of RP. In our study, we found that downgrading independently increased the risk of CSM by 45%, indicating that those tumors may be more aggressive compared with those with lower Bx GG, even though the final whole gland GGs were the same.…”
Section: Discussionmentioning
confidence: 91%
“…Based on that, the authors suggested that Bx grade could add additional prognostic value and may be used for risk stratification. Chung et al 13 in another study also reported an adverse impact of downgrading on biochemical recurrence, with 38% (332/860) of PCa patients downgraded to GS ≤ 7 at time of RP. In our study, we found that downgrading independently increased the risk of CSM by 45%, indicating that those tumors may be more aggressive compared with those with lower Bx GG, even though the final whole gland GGs were the same.…”
Section: Discussionmentioning
confidence: 91%
“…This classification is based on disease characteristics such as stage, grading and prostate specific antigen (PSA) levels [2][3][4][5]. Important known unfavorable histological prognostic features, such as high grade cancer (Gleason grade ≥ 4/ Prognostic Grade Group System ≥4) [6][7][8], vascular lymphatic invasion, extraprostatic extension and advanced stage p disease [9], are not prognostic reliable predictors as opposed to periodic serum PSA level assay, which is now considered the gold standard for PCa monitoring. Although new histopathological diagnostic approaches are emerging, such as early detection of neoplasia [10][11][12][13], there are still a few studies on the validation of proteomic markers.…”
Section: Introductionmentioning
confidence: 99%